The politics of green transformations / pathways to sustainability - Scoones, Ian; Leach, Melissa; Newell, Peter (2015)
"Recalling past transformations, this book examines what makes the current challenge different, and especially urgent. It analyses how green transformations must take place in the context of the particular moments of capitalist development, and in relation to particular alliances. The book emphasises the role of the state and the role of citizens, as innovators, entrepreneurs, green consumers and members of social movements. Green transformations must be both 'top-down', involving elite alliances between states and business, but also 'bottom up', pushed by grassroots innovators and entrepreneurs, and part of wider mobilisations among civil society"--
Keywords: Green movement -- Political aspects; Green movement -- Economic aspects; Environmentalism -- Political aspects; Environmentalism -- Economic aspects; BUSINESS & ECONOMICS -- Development -- Sustainable Development; POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Ecology -- Political Aspect